EFFECT OF ANISAKIS SPP. PARASITE ON HUMAN DIGESTION SYSTEM - Endiputra, Osa (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2019)
Anisakis spp. is a genus of parasitic nematode which can be transmitted to human through seafood like fish and marine mammals. Anisakis may cause health problems in digestive system and allergic reactions when a raw or undercooked fish containing anisakis larvae in third stage of life is consumed. Three species have evidently caused diseases for human: Anisakis simplex sensu stricto, Anisakis simplex C and Anisakis pegreffi. The main symptoms are abdominal pain, nausea, vomiting and urticaria. Some larvae are resistant to heat and digestive enzymes, thus, incidents of this worm induced disease still occur.